Enhancing making every contact count (MECC) training and delivery for the third and social economy (TSE) sector: a strategic behavioural analysis. - Nichol, Beth; Haighton, Catherine; Wilson, Rob; Rodrigues, Angela M. (Psychology & Health, 2025)
Objective: To enhance Making Every Contact Count (MECC, an opportunistic approach to health promotion), training in the Third and Social Economy (TSE, all groups and organisations primarily working towards social justice, outside of the government or household) by examining the degree to which the behavioural content of MECC training tackled significant factors influencing MECC delivery. Methods and Measures: A strategic behavioural analysis design. Semi-structured interviews with service providers (n = 15) and users (n = 5) were coded for barriers and facilitators of MECC delivery using the Theoretical Domains Framework (TDF). Existing MECC training was coded for behaviour change techniques (BCTs) and intervention functions (IFs). The degree to which BCTs and IFs addressed the key TDF domains of influences on MECC delivery in the TSE were examined using prespecified tools. Results: Seven key TDF domains of influences in MECC delivery were identified. Overall, only 9/31 linked BCTs were utilised within MECC training, with percentage utilisation of relevant BCTs for each domain ranging from 0% to 66.7%. Training adequately addressed 2/7 key domains. Conclusion: The TSE and healthcare share many common key TDF domains, although there are differences in how each are relevant. Limitations and recommendations for MECC training are discussed.